Transoral ultrasound: a helpful and easy diagnostic method in obstructive salivary gland diseases - Schapher, Mirco; Goncalves, Miguel; Mantsopoulos, Konstantinos; Iro, Heinrich; Koch, Michael (European Radiology, 2019)
• Transoral ultrasound is a simple technique, very helpful for the evaluation of obstructive diseases of the salivary glands. • It overcomes most of the limitations of transcutaneous ultrasound.
CRIS-Team Scopus Importer:2019-05-02